Шпион Наполеона - Лоран Шарль (Тайны истории в романах, повестях и документах, 1995)
Экземпляры: ф. 20 (20210705) / Инвентарный номер: 6180 / Цена: 20.00 / Авт.знак: Л78 / ГРНТИ: 17.82 / ББК: 84(4Фра)